Materials analysis by aberration-corrected STEM - Krivanek, O; Bacon, N; Corbin, G; Dellby, N; McManama-Smith, A; Murfitt, M; Nellist, P; Szilagyi, Z (2005)
Electron-optical aberration correction has recently progressed from a promising concept to a powerful research tool. 100-120 kV scanning transmission electron microscopes (STEMs) equipped with spherical aberration (C-s) correctors now achieve sub-A resolution in high-angle annular dark field (HAADF) imaging, and a 300 kV C-s-corrected STEM has reached 0.6 A HAADF resolution. Moreover, the current available in an atom-sized probe has grown by about 10x, allowing electron energy loss spectroscopy (EELS) to detect single atoms. We summarize the factors that have made this possible, and outline likely future progress.